VExSearch: Improving Visualizations Results for Web-based Information Exploration and Refinement - Mahdi M.N.; Ahmad A.R.; Ismail R.; Buhari A.M. (International Association of Engineers, 2023)
Visualization; Websites; Class of methods; Cloud computing platforms; Essential features; Exploratory research; Exploratory search; Interactive graphics; Web search results; Web-based information; Search engines